2021
DOI: 10.1140/epjs/s11734-021-00234-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and FPGA implementation of TRNG based on a new multi-wing attractor in Lorenz chaotic system

Abstract: This paper presents a new way of designing a multi-wing chaotic system. The proposed design is based on 3D continuous chaotic system of Lorenz, improved by introducing a saw-tooth and sine functions. The basic proprieties of the proposed system are analyzed using of equilibrium points, phase portrait, Lyapunov exponent, and bifurcation diagram. Furthermore, the modeling of the design is based on Euler method using hardware description language (VHDL) and validated on Xilinx Virtex-II-Pro FPGA platform. Fixed-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Azzaz et al [4] present a new way of designing multiwing chaotic systems. The proposed design is based on a 3D continuous chaotic Lorenz system, improved by introducing saw-tooth and sine functions.…”
Section: Contributed Papers In This Special Issuementioning
confidence: 99%
“…Azzaz et al [4] present a new way of designing multiwing chaotic systems. The proposed design is based on a 3D continuous chaotic Lorenz system, improved by introducing saw-tooth and sine functions.…”
Section: Contributed Papers In This Special Issuementioning
confidence: 99%
“…In order to prevent important information from being illegally stolen during transmission, researchers have introduced many information protection methods, among which the encryption method based on chaos theory has received extensive attention. With the continuous deepening of the exploration of chaotic systems, researchers have discovered many complex dynamic behaviors of chaotic systems, encompassing hyperchaotic phenomena [1][2][3], multi-scroll chaotic attractors [4][5][6], multi-wing chaotic attractors [7][8][9], and hidden chaotic attractors [10][11][12]. Concurrently, researchers have also found that the characteristics of chaotic systems, such as ergodicity, unpredictability, extreme sensitivity to initial conditions, and pseudo-randomness, are strikingly similar to those of cryptography.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32]. Based on the literature, it is possible to again highlight the benefits of programmable devices that exploit mainly three sources of entropy: noise [33][34][35], chaos [36][37][38], and jitter [39][40][41]. As indicated in [42], TRNGs based on jitter are typically easier to integrate and are distinguished by having portable implementations.…”
Section: Introductionmentioning
confidence: 99%